Bacterial Profile and Multiplex PCR Detection of SHV, CTX-M, and mecA Genes in Diabetic Ulcer Infections - Amellya Octifani; Siti Nur Azizah Binti Fandik; Yulianto Ade Prasetya (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2026)
Diabetes mellitus is a chronic disease with complications such as diabetic ulcers, which can lead to amputation. High blood glucose facilitates a mix of aerobic and anaerobic bacterial growth in ulcers. Prolonged antibiotic use risks resistance. This study aims to identify bacterial species and the presence of resistance genes (SHV, CTX-M, and mecA) in isolates from diabetic ulcer patients at Wahidin Hospital, Mojokerto, using multiplex PCR. The study design was a descriptive, observational study to identify bacterial patterns and detect the presence of SHV, CTX-M, and mecA genes in bacterial samples from ulcers of diabetic patients using a multiplex molecular genetic method. Bacterial identification of 32 ulcer swab samples from DM patients revealed Staphylococcus aureus (63%), Escherichia coli (28%), and Klebsiella pneumoniae (9%). The results of the detection of multiplexed genes encoding resistance in the identified bacteria were SHV 3%, CTX-M 19%, mecA 22%, SHV & mecA 3%, and CTX-M & mecA 3%. The multiplex PCR method was successfully used to detect genes encoding antibiotic resistance in bacteria infecting ulcers of patients with DM.